Development of a High-Throughput Calcium Mobilization Assay for CCR6 Receptor Coupled to Hydrolase Activity Readout - Sara Gómez-Melero; Fé Isabel García-Maceira; Tania García-Maceira; Verónica Luna-Guerrero; Gracia Montero-Peñalvo; Javier Caballero-Villarraso; Isaac Túnez; Elier Paz-Rojas (Biomedicines, 2022)
CCR6 is a chemokine receptor highly implicated in inflammatory diseases and could be a potential therapeutic target; however, no therapeutic agents targeting CCR6 have progressed into clinical evaluation. Development of a high-throughput screening assay for CCR6 should facilitate the identification of novel compounds against CCR6. To develop a cell-based assay, RBL-2H3 cells were transfected with plasmids encoding β-hexosaminidase and CCR6. Intracellular calcium mobilization of transfected cells was measured with a fluorescent substrate using the activity of released hexosaminidase as readout of the assay. This stable, transfected cell showed a specific signal to the background ratio of 19.1 with low variability of the signal along the time. The assay was validated and optimized for high-throughput screening. The cell-based calcium mobilization assay responded to the specific CCR6 ligand, CCL20, in a dose-dependent manner with an EC50 value of 10.72 nM. Furthermore, the assay was deemed robust and reproducible with a Z’ factor of 0.63 and a signal window of 7.75. We have established a cell-based high-throughput calcium mobilization assay for CCR6 receptor. This assay monitors calcium mobilization, due to CCR6h activation by CCL20, using hexosaminidase activity as readout. This assay was proved to be robust, easy to automate and could be used as method for screening of CCR6 modulators.